The Morphosynthesis of Event Portfolios: Connecting Networks and the Community - Ziakas, Vassilios (Frontiers in Sports and Active Living, 2022)
Despite the increasing employment of event portfolios by cities and regions to obtain a number of gains, there is a rather slow response from the academic community to fully understand this complex phenomenon and its potential social value. To address this asymmetry furthering the gap between scholarship and practice, the purpose of this article is to theorize the generative mechanisms that shape portfolios as social systems. Based on up-to-date theoretical development, I attempt in this paper to formulate a comprehensive theory of the integrative portfolio nature that interconnects its contextual, policy, operational, and sociocultural dimensions. I do so, by delineating the connective properties of portfolios to assemble different events and enable stakeholders to work toward the accomplishment of common portfolio goals, and by elaborating on the exigencies of portfolios for contributing to the strengthening of the host community's social fabric. This relational analysis operationalizes latest event portfolio elaborations integrated with the perspectives of community capacity-building and quality of life in order to underpin the formulation of a broader framework accounting for the intersection between strategic portfolio planning and the dynamics of stakeholder attitudes, participation in, and community engagement with portfolios. On these grounds, I suggest a new conceptual lens named “morphosynthesis” to explain the multilevel integration processes that shape event portfolios and enable the interlinking of social networks and the community through the array of events. Morphosynthesis constitutes a transdisciplinary perspective that situates the study of event portfolios as a new autotelic subdiscipline across event management, leisure, sport, culture, and tourism. It provides solid but flexible theoretical logics and heuristic means to navigate in the over-fragmented landscape of events and allied industries with the purpose to enhance their compound social value.